Síndrome metabólico en pacientes tratados con antipsicóticos del Albergue para desamparados Divina Misericordia de la ciudad de Machala. - Moreno Moreno, José Xavier (2016)
The Metabolic syndrome is a set of criteria such as central obesity, hypertriglyceridemia, hyperglycemia, low HDL cholesterol and high blood pressure; factors which together may increase the risk of cardiovascular disease or diabetes mellitus, in psychiatric patients this risk increases three times more than the general population for that reason the study was conducted: "METABOLIC SYNDROME IN PATIENTS TREATED WITH ANTIPSYCHOTICS IN THE SHELTER FOR THE HOMELESS PEOPLE OF THE DIVINA MISERICORDIA OF THE CITY OF MACHALA " the goals outlined in the research were to determine the frequency of metabolic syndrome in patients treated with antipsychotics, determine the criteria which mostly present, identify habits that occur in pathients in the study group and establish the drug that fundamentally affects their development. The study was cross-descriptive with quantitative approach, performed in 40 patients in the Shelter for the homeless people of the Divina Misericordia of the City of Machala, medical history and values of laboratory test was managed to obtain research data , with the following results: the prevalence was 62.50%, the criteria mostly occurred in patients were central obesity in 62.50% and 55.50% hypertriglyceridemia, lifestyle was presented in 75.00% and antipsychotic drugs was mostly used in pathiens whit Metabolic Syndrome was therapy he combined between Quetiapine, Risperidone Levomepromazine whith 56.00%, the Quetiapine was used in all patiens with metabolic syndrome, but this studycould not proved his influence for development. KEYWORDS: Metabolic syndrome, antipsychotics, Psychiatric Patients.